2001
DOI: 10.1051/0004-6361:20010303
|View full text |Cite
|
Sign up to set email alerts
|

IXAE observations of the X-ray pulsar XTE J1946+274

Abstract: Abstract.We report results from two observations of the transient binary X-ray pulsar XTE J1946+274 with the Indian X-ray Astronomy Experiment (IXAE) made in September 18-30 1999 and June 28-July 7 2000. The pulsar has a ∼80 days orbital period during which the X-ray intensity varies almost sinusoidally between intensity levels of 5 and 50 mCrab. The mid-time of the two observations with the IXAE are separated by an orbital phase of 0.56 and were in the decaying and rising parts of its orbital modulation, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 2 publications
3
17
0
Order By: Relevance
“…The 2010 RXTE and Suzaku pulse profiles of XTE J1946+274 are double-peaked with a deep and a shallow minimum that show weak energy dependence of the depths (Figure 3). This structure is strongly similar to what has been observed by Wilson et al (2003) and Paul et al (2001) during the 1998 outburst with other instruments at different luminosities. The source even shows a double-peaked profile during quiescence as observed by Chandra (Özbey Arabacı et al 2014).…”
Section: Accretion Columnsupporting
confidence: 89%
“…The 2010 RXTE and Suzaku pulse profiles of XTE J1946+274 are double-peaked with a deep and a shallow minimum that show weak energy dependence of the depths (Figure 3). This structure is strongly similar to what has been observed by Wilson et al (2003) and Paul et al (2001) during the 1998 outburst with other instruments at different luminosities. The source even shows a double-peaked profile during quiescence as observed by Chandra (Özbey Arabacı et al 2014).…”
Section: Accretion Columnsupporting
confidence: 89%
“…Several weaker outbursts followed the first one from 1998 to 2001 (Campana et al 1999;Paul et al 2001;Wilson et al 2003). Similar behaviour has been also observed in other Be systems (see for example Caballero et al 2013).…”
Section: Introductionsupporting
confidence: 70%
“…The two peaks are separated by about half a phase, and, therefore, likely represent two emission components with roughly orthogonal beam patterns. Paul et al (2001) suggested that the two peaks might be related to the emission from the two poles of the neutron star not diametrically positioned to each other. On the other hand, the pulse profile evolution, and in particular the ∼ 180…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 0.1 s time resolution in the Medium mode restricts the observation of QPOs up to 5 Hz only, while the 1 s resolution restricts the reporting of QPOs up to 0.5 Hz only. Nevertheless, the light curves are clear enough and the identification of the specific class can be done without ambiguity (e.g., Naik et al 2001Naik et al , 2002bPaul et al 2001). It is to be noted that (a) the counts in the high energy bin could be very low and the s φ suffers from low number statistics; and (b) the slope itself is known to vary in the 2−18 keV range, especially, the spectrum becomes harder above 10−12 keV in the hard state.…”
Section: Observation Of Class Transitionsmentioning
confidence: 99%